Benefits of the Proposed Magia Mission for Lunar Geology - Massironi, M.; Giacomini, L.; Ferrari, S.; Martellato, E.; Cremonese, G.; Marchi, S.; Coradini, A. (Discover Space, 2010)
Age of geological units, surface mineralogical composition, volcanism, tectonics and cratering are major keys for unravelling the geodynamic and geological history of a planet. Thanks to the extensive exploration of the 1960s and 1970s and the compositional mapping of the 1990s missions (Galileo, Clementine and Luna Prospector), the Moon has a unique geological dataset among the extraterrestrial Solar System bodies. The recent and on-going missions, along with the future plans for lunar exploration, will together acquire an extraordinary amount of data. This should provide a solid basis to meet broad objectives like the constraints on the heterogeneity of Lunar composition and the presence of water deposits, the understanding of volcanic and tectonic evolution as well as more specific issues such as the genetic classification of volcanic domes, origin of the dark-halos craters, lava flow emplacement mechanisms, and the kinematics and deformational styles of tectonic structures. The Italian small mission MAGIA (Missione Altimetrica Gravimetrica geochImica lunAre) will be equipped with an integrated context camera and imaging spectrometer, a high resolution camera and a radar altimeter. The spatial and spectral resolution of these instruments will provide data products complementing past and ongoing Lunar mission data, particularly for the polar regions where a full resolution coverage is planned. A general review of some still unanswered questions on lunar surface composition, cold traps, volcanism, tectonics and cratering records is presented here in order to illustrate the potential contribution of MAGIA to these subjects.